36-(3c+4)=3(c+7)+c

Simple and best practice solution for 36-(3c+4)=3(c+7)+c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36-(3c+4)=3(c+7)+c equation:


Simplifying
36 + -1(3c + 4) = 3(c + 7) + c

Reorder the terms:
36 + -1(4 + 3c) = 3(c + 7) + c
36 + (4 * -1 + 3c * -1) = 3(c + 7) + c
36 + (-4 + -3c) = 3(c + 7) + c

Combine like terms: 36 + -4 = 32
32 + -3c = 3(c + 7) + c

Reorder the terms:
32 + -3c = 3(7 + c) + c
32 + -3c = (7 * 3 + c * 3) + c
32 + -3c = (21 + 3c) + c

Combine like terms: 3c + c = 4c
32 + -3c = 21 + 4c

Solving
32 + -3c = 21 + 4c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4c' to each side of the equation.
32 + -3c + -4c = 21 + 4c + -4c

Combine like terms: -3c + -4c = -7c
32 + -7c = 21 + 4c + -4c

Combine like terms: 4c + -4c = 0
32 + -7c = 21 + 0
32 + -7c = 21

Add '-32' to each side of the equation.
32 + -32 + -7c = 21 + -32

Combine like terms: 32 + -32 = 0
0 + -7c = 21 + -32
-7c = 21 + -32

Combine like terms: 21 + -32 = -11
-7c = -11

Divide each side by '-7'.
c = 1.571428571

Simplifying
c = 1.571428571

See similar equations:

| 2(x-4)=3x+11 | | W=mb-r | | 4x-3(2-3x)=4(x-4)-17 | | 5.05t=1.48t-3.57 | | -7/2r=-63/8 | | 2x+2y+3x+6y= | | 2(x-4)=2x+11 | | z+8=12-z | | Z=a-b+c | | 0=56x^2-72x+144 | | 16x^2-4x+252=0 | | 3/17=x/7 | | x=3-14 | | -2x=-54 | | (V+3)2=28 | | 4y-40=8y | | ((5Y^6)/(3Y^4))^(1/5) | | 4-y+2=-4 | | 17x^2+11x-6=0 | | 2(q-29)=1/2(4-8q) | | 3n^2=-12n-7 | | v+3squared=28 | | 5x-7/4=1/3 | | 6x+3=8x-17 | | Y=x^2+6-1 | | 10x+73+6x=-15+x | | -1=3+4k | | 3[2(x-3)+2]+5(x-3)=0 | | 5x+2(x+4)=60+3x | | 8.4-0.7t+2.2-1.4t=9-2.1t-6.4 | | 6(x-7)=12(x+4) | | f(2)+f(3)=f(5) |

Equations solver categories